Pendidikan Islami dalam Pemikiran Hasan Langgulung - Badruzaman, Badruzaman; Hafidhuddin, Didin; Mujahidin, Endin (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
Langgulung is an expert on Muslim education, in which he asserted that the source of the main runway and the Islamic education curriculum is Islamic teachings (al-Qur'?n and as-Sunnah). However, Langgulung is not a person who shut to use the source in addition to Islam, to the extent that relevant sources and does not conflict with the main runway. Therefore, one of the cornerstone of Islamic education curriculum arrangement is the one of the implementations of the alignment is the adjustment with the development of science. This indicates the existence of a dynamic and open in the thought of Langgulung. View of dynamic of education curriculum implications in an effort renewal curriculum that didn’t outdated, so always up to date. The journal is a library research. Data writing techniques emphasize text analysis and study, library research is done by collecting literature related to research material, whether in the form of books, magazines, articles or opinions and the primary book in this research is the book of Man and Education: A Psychological Analysis and Education, Principles of Islamic Education, Islamic Education and Civilization, Creativity and Islamic Education: Analysis of Psychology and Philosophy, Islamic Education Faces the 21st Century, Some Thoughts on Islamic Education by Hasan Langgulung. According to Hasan Langgulung; humans are essentially created to carry out the duty of service to the creator (‘abdullah) and his duty as the caliph of Allah (Khal?fatullah) on the face of the earth. The purpose in humans with the religion of Islam is: (1) so that humans carry out their functions as caliphs, and (2) so that humans always serve God. The purpose of this human formation will intersect with the objectives of Islamic religious education, because education is basically to reach people of faith and charity.